Retos Compartidos a la Integración y el Desarrollo. Un Análisis de Largo Alcance - Anthony P. Maingot (Études Caribéennes)
This essay makes an empirical comparison of four major challenges to the integration and development of the independent countries of the Caribbean. It hypothesizes a series of geopolitical and geo-economic difficulties which portends problems in the medium to longer term. Their inability to act collectively weakens their ability to deal with the chanllenges.